A Part-of-Speech Tagset for Morphosyntactic Tagging of Amharic - Krzyżanowska, Magdalena (Aethiopica, 2017)
The aim of the article is to propose a tagset for the morposyntactic tagging of Amharic and to discuss those issues which may seem problematic. The tagset contains forty-seven tags grouped into twelve parts of speech. It is hoped that it provides a starting point for more exhaustive guidelines for prospective annotators.